We see the same sun : CD sampler - Mr. President; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music, 1997)
Contains samples of four tracks from one of the most successful German pop band taken from the album We See The Same Sun.
CD 1 : Show Me The Way / (3:30) -- I Give You My Heart / (3:35) -- I Love To Love / (3:10) -- Coco Jamboo / (3:38).
Koleksi Khas Wiramanja.
T-Seven, Lady Danii, Lazy Dee.
Title from disc label.
Keywords: Songs, English